Manufacturing and Evaluating of Indirect Solar Dryers: A Case Study for the Kurdistan Region of Iraq - Khidir, Dara K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
–Indirect solar drying uses solar radiation to heat air and dry agricultural products in harvest time to store them for a longer time and reduce waste. The dryer consists of a solar air heater collector, a drying chamber, and an air ventilation system. In this study, an indirect solar dryer system is constructed and ventilated with an electrical fan. Experiments are conducted on the system using eggplant as an agricultural sample on 2 consequent days (29th and 30th October 2022), to evaluate the system data recorded during the drying process in terms of the temperature for points in the system, solar radiation, and the sample mass. The temperature measurements are ambient, collector, and dried chamber outlet temperatures. The results show that the most effective time for solar drying is between 9:00 and 16:00, and the drying system air temperature is raised to about 40°C when solar radiation reached more than 600 W/m2 in the noon time. The weighted mass is used to evaluate the drying process, and maximum drying rate and drying efficiency are obtained on the 1st day of the drying before noon time.